ALGEBRAIC INTEGERS OF PURE QUARTIC EXTENSIONS - de Andrade, Antonio Aparecido; Facini, Linara Stéfani; Esteves, Livea Cichito (Academic Publications, 2023)
Let Q denote the field of rational numbers and K be a pure quartic extension, that is, K = Q(4√d), where d is a square free integer. In this work, we present an integral basis, norm, trace and the discriminant of K.
Keywords: algebraic integers; pure quartic extensions